2018
DOI: 10.1038/s41477-018-0249-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome encode analyses reveal the basis of convergent evolution of fleshy fruit ripening

Abstract: Fleshy fruits using ethylene to regulate ripening have developed multiple times in the history of angiosperms, presenting a clear case of convergent evolution whose molecular basis remains largely unknown. Analysis of the fruitENCODE data consistint of 361 transcriptome, 71 accessible chromatin, 147 histone and DNA methylation profiles reveals three types of transcriptional feedback circuits controlling ethylene-dependent fruit ripening. These circuits are evolved from senescence orfloral organ pathways in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
242
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 294 publications
(251 citation statements)
references
References 28 publications
7
242
0
2
Order By: Relevance
“…All of these considerations indicate that more extensive research is required on the function of the ethylene perception and signaling components, MADS‐RIN and other MADS proteins and NAC‐NOR and other NAC family members in ripening fruits. This is particularly important in the light of the recent evidence from the analysis of regulatory circuits and gene promoters in different fruits that there are at least three distinct regulatory loops controlling ethylene biosynthesis genes in different fruit types, with MADS‐RIN playing a central role in some fruits and NAC‐NOR taking on this role in others (Lü et al ., ). Fleshy fruit ripening developed several times during angiosperm evolution and there is a multitude of varieties and cultivars of fruits with subtle differences in ripening behavior.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All of these considerations indicate that more extensive research is required on the function of the ethylene perception and signaling components, MADS‐RIN and other MADS proteins and NAC‐NOR and other NAC family members in ripening fruits. This is particularly important in the light of the recent evidence from the analysis of regulatory circuits and gene promoters in different fruits that there are at least three distinct regulatory loops controlling ethylene biosynthesis genes in different fruit types, with MADS‐RIN playing a central role in some fruits and NAC‐NOR taking on this role in others (Lü et al ., ). Fleshy fruit ripening developed several times during angiosperm evolution and there is a multitude of varieties and cultivars of fruits with subtle differences in ripening behavior.…”
Section: Discussionmentioning
confidence: 97%
“…The results of Lü et al . () remind us that new ripening genes can be recruited or removed from the ripening program by acquisition or deletion of the appropriate TF‐binding motifs in their promoters, thus changing their regulation. With the technologies now available we can expect further rapid improvements in our understanding of the mechanistic variations underlying the biological diversity of ripening behavior in different fruits.…”
Section: Discussionmentioning
confidence: 99%
“…). Second, this leads to the induction of RIN (Giovannoni et al , ; Li et al , ; Lü et al , ). The effect of ET on RIN transcripts was quantified in our previous experiments (Li et al , ) and we found that RIN mRNA was reduced 4‐5‐fold by treating MG WT fruit with 1‐MCP compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ET on RIN transcripts was quantified in our previous experiments (Li et al , ) and we found that RIN mRNA was reduced 4‐5‐fold by treating MG WT fruit with 1‐MCP compared to the control. RIN and TAGL1 also may be involved in a positive feedback loop leading to system‐2 ET production, because ET biosynthesis genes have been reported to be directly targeted by a RIN‐TAGL1 complex (Lü et al , ). We propose a working model (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation